Jeffrey’s insights: Jeffrey Modell Foundation’s global genetic sequencing pilot program to identify specific primary immunodeficiency defects to optimize disease management and treatment - Jessica Quinn; Vicki Modell; Jennifer Holle; Rebecca Truty; Swaroop Aradhya; Britt Johnson; Jordan Orange; Fred Modell (Immunologic Research, 2020)
Primary immunodeficiencies (PI) are genetic defects of the immune system that result in chronic and often life-threatening infections and/or life-threatening autoimmunity if not diagnosed and treated. Patients with a suspected PI, but without a genetic diagnosis, commonly undergo a diagnostic odyssey that is costly, time-consuming, and arduous. This delay in diagnosis prevents appropriate disease management and treatment, contributing to prolonged suffering and decreased quality of life. Although next generation sequencing (NGS) can provide these patients with relief from such a diagnostic odyssey, it is often unavailable, mainly due to cost and inaccessibility. In January 2019, the Jeffrey Modell Foundation (JMF) launched a free genetic sequencing pilot program for Jeffrey Modell Centers Network (JMCN) patients clinically diagnosed with an underlying PI. A total of 21 sites within the JMCN were invited to participate. JMF collaborated with Invitae, and testing was comprised of Invitae’s Primary Immunodeficiency Panel, which currently includes 207 genes. A questionnaire was disseminated to each participating physician to evaluate barriers to access to genetic sequencing and changes in disease management and treatment after testing. One hundred fifty-eight patients and 29 family members were tested in this pilot study. Twenty-one percent of patients with a suspected monogenic disorder received a molecular diagnosis, and others received potentially useful diagnostic leads. Based on the results of genetic sequencing, clinical diagnosis was altered in 45% of patients, disease management was altered in 40%, treatment was altered in 36%, and genetic counseling was altered in 62%. The results of this pilot program demonstrate the utility, cost-efficiency, and critical importance of NGS for PI and make the case for broad scale sequence–based diagnostics for PI patients when requested by expert immunologists.

The case for severe combined immunodeficiency (SCID) and T cell lymphopenia newborn screening: saving lives…one at a time - Jessica Quinn; Jordan S. Orange; Vicki Modell; Fred Modell (Immunologic Research, 2020)

Global report on primary immunodeficiencies: 2018 update from the Jeffrey Modell Centers Network on disease classification, regional trends, treatment modalities, and physician reported outcomes - Vicki Modell; Jordan S. Orange; Jessica Quinn; Fred Modell (Immunologic Research, 2018)

Modeling strategy to identify patients with primary immunodeficiency utilizing risk management and outcome measurement - Vicki Modell; Jessica Quinn; Grant Ginsberg; Ron Gladue; Jordan Orange; Fred Modell (Immunologic Research, 2017)

Primary immunodeficiencies worldwide: an updated overview from the Jeffrey Modell Centers Global Network - Vicki Modell; Jessica Quinn; Jordan Orange; Luigi D. Notarangelo; Fred Modell (Immunologic Research, 2016)

Global overview of primary immunodeficiencies: a report from Jeffrey Modell Centers worldwide focused on diagnosis, treatment, and discovery - Vicki Modell; Megan Knaus; Fred Modell; Chaim Roifman; Jordan Orange; Luigi D. Notarangelo (Immunologic Research, 2014)

An analysis and decision tool to measure cost benefit of newborn screening for severe combined immunodeficiency (SCID) and related T-cell lymphopenia - Vicki Modell; Megan Knaus; Fred Modell (Immunologic Research, 2014)

Global study of primary immunodeficiency diseases (PI)—diagnosis, treatment, and economic impact: an updated report from the Jeffrey Modell Foundation - Vicki Modell; Bonnie Gee; David B. Lewis; Jordan S. Orange; Chaim M. Roifman; John M. Routes; Ricardo U. Sorensen; Luigi D. Notarangelo; Fred Modell (Immunologic Research, 2011)

From genotype to phenotype. Further studies measuring the impact of a Physician Education and Public Awareness Campaign on early diagnosis and management of Primary Immunodeficiencies - Fred Modell; Diana Puente; Vicki Modell (Immunologic Research, 2009)

Impact of a physician education and patient awareness campaign on the diagnosis and management of primary immunodeficiencies - Diana Pickett; Vicki Modell; Ian Leighton; Fred Modell (Immunologic Research, 2008)

The impact of physician education and public awareness on early diagnosis of primary immunodeficiencies - Vicki Modell (Immunologic Research, 2007)